Scientific Research and Covid-19: Reconsidering Paradigms. - Medina Borges, Rosa María (Medicina Clínica y Social, 2021)
ABSTRACT: The present article has been written from the critical research paradigm with the following objective: to reflect about the necessity of reconsidering current research paradigms due to the new reality imposed by Covid-19 pandemic. It includes the theoretical postulates about the usefulness of research paradigms, the dilemma of carrying out scientific research on SARS-CoV-2 and Covid-19 in such short periods of time, the theoretical and methodological contributions of critical epidemiology, and the implementation of some methodological assumptions of critical epidemiology in the current fight against Covid-19 in Cuba. Several points of view which the author endorses are also presented.
Keywords: scientific research, coronavirus infection, research paradigms, critical epidemiology, Cuba